Potensi Pasar UMKM Halal Dalam Perekonomian Indonesia - Sari, Mutiara (El-kahfi | Jurnal Ekonomi Islam, 2023)
The halal UMKM market is expected to help strengthen the country's economy, along with the recovery of world economic growth after the epidemic. There are potentials that can increase the growth of the halal UMKM market, including the world's sizable muslim population and the increasing global consumption of halal products. The Indonesia Halal Markets 2021-2022 report shows that the world's muslim population has spent US$1.9 trillion on the consumption of halal products in 2020. This study aims to analyze the market potential of halal UMKMs in the Indonesian economy. This research method is descriptive qualitative using secondary data from journals, documented books, and relevant publications. The results show that by utilizing the huge market potential around the world, both in muslim and non-muslim countries, Indonesian halal UMKMs can provide great benefits and strengthen the Indonesian economy. This is supported by the promotion of halal lifestyle which is universal so that it can make the world community aware of the halal function of a product guaranteed by halal certification. The Indonesian government has taken various steps to expand the Indonesian halal UMKM market so that it can compete globally, which can help the nation's economy.